Augmented Physics’ Lab: Magnetic Field Use Virtual Learning Media for 21st Century Students - Dadan Sumardani; Agustiani Putri; Zulri Ramadhan; Fauzi Bakri; Dewi Muliyati (Jurnal Pembelajaran Fisika, 2020)
The 21st century has brought a paradigm change that shifts conventional learning towards technology-based learning. PISA data shows that Indonesia only achieved a score of 382, while TIMSS stated that the percentage of correct answers to the problem of understanding was always higher than the matter of application. This indicates that HOTS students in Indonesia have not yet developed optimally. This investigation intends to create worksheets for students implemented by augmented reality on magnetic field substance. This investigation was development research which used the Dick and Carey method. The product can display 3-Dimensional simulations. According to an investigation, the validation result of the students’ worksheets already met the criteria very well in terms of material with a percentage of 95%, in terms of media with a percentage of 86.8% and terms of learning with a percentage of 81%, and product trials by teachers with a percentage of 98%. Meanwhile, trials of students obtained an N-gain result of 0.64 which interpreted an increase in students' high-level thinking skills in the medium level. Therefore, it could be assumed that augmented physics' lab has been suitable for students' higher-order thinking skills.Keywords: Augmented Reality, HOTS, Virtual LearningDOI: http://dx.doi.org/10.23960/jpf.v8.n1.202007